MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN MINAT BELAJAR AKIDAH AKHLAK - Muammar, Muammar; Suhartina, Suhartina (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2018)
This study aims to describe the application of learning media in increasing the interest in learning Aqidah Akhlak for students of MTs DDI Pacongang Pinrang. This type of research is descriptive qualitative research. Data is obtained through observation, interviews, and documentation. The results showed that the use of audio-visual learning media is very supportive in learning activities, especially in learning Aqidah Akhlak . The pesetas students are very motivated when the learning uses the laptop/computer media, projector / LCD, and internet speaker network. In addition, the use of learning media in MTs DDI Pacongang has an important role in student learning interests, including feelings of joy and increased interest in the material. The implication of this study is that the teacher in delivering the learning material in the classroom must be clever in choosing the right media, the teacher must have creative and innovative ideas so that the learning atmosphere of students is more motivated and motivated.